Mobility and spatial planning in the Lisbon Metropolitan Area - Santos,Sofia (2017)
Peoples daily mobility and commuting patterns are differentiated by sociodemographic features. It relates to place as structure (spatial organization) and to public policy (spatial planning). Between urban structure and peoples traveling behaviours, spatial public policy should be called to reduce social inequality and to promote more just territories. This concerns the process of planning as well as its outcomes. Accessibility and conflict are important questions to be approached in both. The paper examines the importance of social issues in the design of the Lisbon Metropolitan Areas (LMA) policies on mobility and spatial planning. It continues to be a peripheral matter, despite some change at the discursive level. We begin by discussing how spatial justice and social inequalities can be central to mobility and spatial planning. Secondly, the general European and national policy background is presented. Finally, some fundamental trends of LMA mobility statistics are outlined followed by a critical reading of municipal and supramunicipal mobility related policies